Sistem Informasi Perpustakaan Terintegrasi Digital - Yusniah Yusniah; Nurhayati Gultom; Suci Wahyu Tami Br Rambe; Zul Fikar Husein (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Libraries are expected to be able to take an important and central role in providing library assistance (Subroto, 2009). The data collection method used in this study is a case study. The term library is also defined as a media center, learning center, educational resource, information center, documentation center and reference center (The American Library Association cited by Mahmudi, 2006). The result of this research is a digital Integrated Library Information System, which presents variants of book information in the concept of e-library or digital library. Key Note: Library Information System, digital and Media